2009
DOI: 10.1017/s1366728909990216
|View full text |Cite
|
Sign up to set email alerts
|

Development of English referring expressions in the narratives of Chinese–English bilinguals

Abstract: This paper investigates the development of referring expressions in the narratives of children learning English as a second language (L2). Spoken narratives in English were elicited from sixty Chinese-speaking participants at four ages – five, eight, ten, and young adults – using the wordless picture bookFrog, where are you?(Mayer, 1969). Narrative analysis focused on the referring expressions that the L2 speakers used to introduce and maintain reference to story characters in the narratives and on the referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Kang (2009) further illustrated how such LI-specific strategies, in combination with the lack of L2 linguistic competence, prevented Korean EFL learners from achieving discourse effects through sophisticated use of referential strategies in their narrative production. Chen and Pan (2009) similarly found that Chinese-English bilinguals' LI practice in the use of referential expressions hindered the development and appropriate use of the same language functions in English. On the other hand, in another study investigating Korean EEL learners' management of conjunctions in their written narratives, Kang (2008) revealed that despite their LI conjunction-managing practice that was quite similar to that of the native English speakers', the Korean EEL learners' use of conjunctions in their L2 (English) was quite different from both their LI and the native English speakers' use of conjunctions as means of discourse coherence, probably due to insufficient practice in linguistic manipulations and discourse production in English.…”
Section: Backgroundsmentioning
confidence: 92%
“…Kang (2009) further illustrated how such LI-specific strategies, in combination with the lack of L2 linguistic competence, prevented Korean EFL learners from achieving discourse effects through sophisticated use of referential strategies in their narrative production. Chen and Pan (2009) similarly found that Chinese-English bilinguals' LI practice in the use of referential expressions hindered the development and appropriate use of the same language functions in English. On the other hand, in another study investigating Korean EEL learners' management of conjunctions in their written narratives, Kang (2008) revealed that despite their LI conjunction-managing practice that was quite similar to that of the native English speakers', the Korean EEL learners' use of conjunctions in their L2 (English) was quite different from both their LI and the native English speakers' use of conjunctions as means of discourse coherence, probably due to insufficient practice in linguistic manipulations and discourse production in English.…”
Section: Backgroundsmentioning
confidence: 92%
“…Through narratives, children learn particular ways to talk about events beyond the sentence level, first, in a conversational context with supportive input from an adult or a peer partner (Eisenberg, 1985), and later, as an autonomous, de-contextualized text produced with little verbal support, showing increasing structural and linguistic complexity towards school-age and beyond (Berman & Nir-Sagiv, 2007;Berman & Slobin, 1994). As a semi-naturalistic arena to study language changes beyond the sentence level, psycholinguistic research on narrative abilities has focused on coherence and cohesion in producing and comprehending discourse (Hickmann, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have used the Frog Story picture book to investigate the relationship between command of linguistic structures, narrative organization and connectivity (e.g., Aarssen, 2001 with Turkish-Dutch bilinguals; Akinçi, Jisa, & Kern, 2001 with Turkish-French bilinguals; Kupersmitt, 2004 with Spanish-Hebrew bilinguals;Minami, 2008 with Japanese-English bilinguals), the expression of evaluative content such as false belief and character's thoughts (e.g., Pearson, 2001 with Spanish-English bilinguals), or the management of referential links (e.g., Chen & Pan, 2009 with ChineseEnglish bilinguals). Overall, these studies revealed similar patterns of structural organization and of discourse-related principles of language use in monolingual and bilingual narratives, which seem to be guided by universal, languageindependent strategies (Berman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Jalongo et al, 2002) • second language learning (e.g. Chen and Pan, 2009) • linguistic and cognitive abilities of children from different language and /or cultural back grounds (since most of these are conducted in the US they usually concern either Spanish, Chinese or African American children) (e.g. Gorman et al, 2011) • home/family literacy research and intervention (e.g.…”
Section: Research Studies From 1998 -2012mentioning
confidence: 99%